Citrate-capped quantum dots of CdSe for the selective photometric detection of silver ions in aqueous solutions - Ingole, Pravin P.; Rajiv M. Abhyankar; Bhagavatula L. V. Prasad; Haram, Santosh K. (Materials Science and Engineering B-Advanced Functional Solid-State Materials, 2010)
A simple strategy for the synthesis of water soluble, luminescent, citrate-capped CdSe quantum dots (Q-CdSe) and their applications to selective detection of silver ions are described. The steady state photoluminescence (PL) spectra show single, narrow emission band at ca. 554 nm without any contribution from the trap states. The effect of various ions including physiologically important metal ions (viz. K(+), Ca(2+), Fe(3+), Zn(2+), Mg(2+), Mn(2+), Cu(2+), Ag(+), Pb(2+) and Cd(2+)), on the PL intensity of citrate-capped Q-CdSe has been studied. Among these, selective luminescence quenching with Ag(+) ion was found to be predominant. Under the optimum conditions, the response was linear between 1.7 and 18 mu M. The quenching constant K(SV) was found to be ca. 3.4 x 10(5) M(-1). The mechanism of photoluminescence quenching of Q-CdSe by metal ions (Ag(+)) is also discussed. Based on these studies, the potential use of Q-CdSe as a luminescent probe for the selective detection of silver ion has been proposed. (C) 2009 Elsevier B.V. All rights reserved.
Conference on Specialty Advanced Materials and Polymers for Aerospace and Defense and Applications (SAMPADA-2008), Mat Res Soc Singapore, Singapore, SINGAPORE, JUL 03-08, 2005
Keywords: Ag(+) ions; Luminescence quenching; Luminescent probe; Q-CdSe; Tri-sodium citrate